NONFORMAL EDUCATION AND REDUCTION OF POVERTY IN RURAL AREAS - Faisal Faisal; Ahamd Risal; Hardianto Hardianto; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2019)
Non-formal education through life skills education has shown a positive contribution to poverty reduction in rural areas, although it still requires efforts to develop various life skills education models through research and development. This is based on the idea that improving the quality of the poor requires a development effort that is carried out in a planned, structured, and based on scientific and objective thinking. This study aims to produce a life skills education model that can play a role in poverty reduction in rural areas. The results showed that: first, the assessment of life skills education needs in the two target groups was carried out using 4-H life skills thinking (head / brain, hands / hands, heart / heart, and health / health). Life skills needs in the target groups in the two programs referred to show conditions that are not much different, where the two groups still need to be developed aspects of the brain, hands, and heart. In addition, a validated 4-H life skills education model was formulated. Second, based on the conditions found, a series of life skills education development activities carried out include vocational training, the provision of learning experiences through field observations, discussions and reflections on vocational training results and observations, implementation of 4-H model non-vocational life skills training, and evaluation of educational outcomes carried out . The development model that was tested was then validated. Evaluation results indicate an increase in educational output held in the two target groups of the program. Therefore, in the context of poverty reduction, the 4-H PKH model needs to be developed in a more structured and integrative way and guarantee all life skills that are the focus of developing life skills to overcome poverty.